The development of cladding materials for the accident tolerant fuel system from the Materials Genome Initiative. (December 2017) - Liu, Zhen; Li, Yifan; Shi, Diwei; Guo, Yaolin; Li, Mian; Zhou, Xiaobing; Huang, Qing; Du, Shiyu
Abstract: The 2011 Fukushima Daiichi disaster raises the requirement of accident tolerant fuel (ATF) cladding. As promising candidates, the FeCrAl ternary alloy and SiC fiber reinforced SiC matrix (SiC/SiC) composites are discussed with details for recent development, as well as the issues of their in-core application and fabrication. Herein, the design of materials based on the Materials Genome Initiative (MGI) is introduced as the effective scheme in accelerating the development for ATF claddings. Correspondingly, the potential technical routes are provided and some examples of preliminary modelling studies as the preparation steps for MGI are presented.